Pediatrician's perception of oral health in children - A qualitative study - Geetha Priya Pollachi-Ramakrishnan; Sharath Asokan; Chandrakantha Balaraman; Sudhandra Viswanath; Yogesh Kumar Thoppe Dhamodharan (Wolters Kluwer Medknow Publications, 2023)
Background: It is important to assess pediatrician's perception on children's oral health as they tend to meet children early on a regular basis. Quantitative research has shown that pediatricians in India have inadequate knowledge and limited awareness about oral health care in children. Hence, it is important to assess pediatrician's opinion and perception on children's oral health using qualitative interview method. Aim: The aim of the study is to assess and explore the perception of pediatricians on children's oral health in Western Tamil Nadu, India. Methods: A grounded theory approach was employed to conduct this qualitative study. Face-to-face interviews with the pediatricians were conducted using a semi-structured interview guide. Interviews were audio-recorded and transcribed verbatim. Collected data were written as codes, from which categories and themes were derived. Results: Four themes arrived: (1) dental health and disease, (2) anticipatory guidance, (3) barriers, and (4) remedial measures. The participants felt that they were underinformed about dental home, emergency care for dental trauma, and the interceptive role of dentists on oral deleterious habits. Insufficient dental information in their curriculum and the absence of common guidelines between pediatricians and pediatric dentists in India were considered the common causes for their lack of knowledge. Conclusion: Pediatricians were receptive to acquire knowledge and improvising their skills. They felt that periodic lectures and formal gatherings should be planned between pediatric dentists and pediatricians. Collaborations between pediatrics and pediatric dentistry societies are warranted to provide children with better oral health care.